(untitled) (Revista Brasileira Multidisciplinar, 2026)
Eucalyptus is widely used in the forestry sector due to its favorable characteristics for timber, paper and cellulose production. Although native to Australia, the species has demonstrated good adaptation to Brazilian climatic conditions. However, the expansion of cultivated areas has favored the emergence and spread of phytopathogens. Among the most relevant diseases, tip dieback stands out, caused by the bacterium Erwinia psidii, with increasing occurrence in nurseries and commercial plantations. In this context, the development of alternative and sustainable management strategies is essential for disease prevention and control. The present study evaluated, through in vitro broth microdilution and disk-diffusion assays, the bactericidal and bacteriostatic effects of eucalyptus essential oil, neem oil, and propolis extract against E. psidii. Six bacterial strains, previously characterized by molecular techniques using specific and universal primers followed by Sanger sequencing, were employed. In vitro results demonstrated that eucalyptus essential oil exhibited bactericidal activity against the phytopathogen, with inhibition halo formation and a minimum inhibitory concentration (MIC) of 5%. The remaining products showed no detectable bactericidal activity under the conditions tested. These findings indicate that eucalyptus essential oil represents a promising alternative for the control of E. psidii under laboratory conditions, contributing to research aimed at reducing the use of synthetic pesticides and promoting the sustainability of eucalyptus forest production.